Pitted keratolysis - Hiram Larangeira de Almeida Jr; Rodrigo Nunes Siqueira; Renan da Silva Meireles; Greice Rampon; Luis Antonio Suita de Castro; Ricardo Marques e Silva (Sociedade Brasileira de Dermatologia, 2016)
Abstract Pitted keratolysis is a skin disorder that affects the stratum corneum of the plantar surface and is caused by Gram-positive bacteria. A 30-year-old male presented with small punched-out lesions on the plantar surface. A superficial shaving was carried out for scanning electron microscopy. Hypokeratosis was noted on the plantar skin and in the acrosyringium, where the normal elimination of corneocytes was not seen. At higher magnification (x 3,500) bacteria were easily found on the surface and the described transversal bacterial septation was observed.